1970
DOI: 10.1177/00220345700490010501
|View full text |Cite
|
Sign up to set email alerts
|

Punch-Shear Test for Dental Purposes

Abstract: Average shear stress may be calculated from the force required to punch a cylinder out of a disk or plate of material. Tests on aluminum and methacrylate sheets enabled the comparison of dental restoratives with human dentin. Human dentin was found to have a greater shear strength than dental restoratives other than gold alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 0 publications
0
30
0
5
Order By: Relevance
“…It has been suggested that this test provides a better evaluation of bond strength than the conventional shear test because in the pushout test, fracture occurs parallel to the dentin-bonding interface, which makes it a true shear test for parallel-sided samples 7,10 . Extrusion testing in dentistry was first described by Roydhouse 11 (1970). Kimura, Shimizu and Fujii 12 (1985) concluded that push-out testing tended to reduce the values for bond strength to dentin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this test provides a better evaluation of bond strength than the conventional shear test because in the pushout test, fracture occurs parallel to the dentin-bonding interface, which makes it a true shear test for parallel-sided samples 7,10 . Extrusion testing in dentistry was first described by Roydhouse 11 (1970). Kimura, Shimizu and Fujii 12 (1985) concluded that push-out testing tended to reduce the values for bond strength to dentin.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A variation in results for some materials, particularly in the shear punch test of uncoated Fuji II LC and in the microhardness of coated Fuji II LC, at different time intervals was observed. These results may be related to the complexity of the stress distribution in a specimen during loading by the punch, 8 as well as the possibility of voids existing within the material that could not be detected prior to testing. The existence of undetectable voids will cause differences in the strengths observed.…”
Section: Roydhousementioning
confidence: 99%
“…The mechanical properties of dental cements have been reported in many studies [1][2][3] . In particular, several researchers have investigated the shear strength of restorative materials using the shear punch test [4][5][6][7][8][9][10][11][12] . Their studies mainly focused on the suitability of the shear test method for restorative filling materials such as resin composites and glass ionomers.…”
Section: Introductionmentioning
confidence: 99%